2010
DOI: 10.1287/mksc.1090.0520
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Branching Model for Predicting the Spread of Electronic Word of Mouth

Abstract: In a viral marketing campaign, an organization develops a marketing message and encourages customers to forward this message to their contacts. Despite its increasing popularity, there are no models yet that help marketers to predict how many customers a viral marketing campaign will reach and how marketers can influence this process through marketing activities. This paper develops such a model using the theory of branching processes. The proposed viral branching model allows customers to participate in a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 28 publications
0
122
0
4
Order By: Relevance
“…Hinz et al [14], for instance, found that seeding viral content among individuals with many social connections was particularly effective in maximising the eventual reach of that content. While van der Lans et al [10] developed a model to examine, in part, the effect that different seeding strategies would have on the viral dissemination of content. This focus on campaign seeding is perhaps a reflection of the difficulties associated with developing or managing other elements of viral marketing campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hinz et al [14], for instance, found that seeding viral content among individuals with many social connections was particularly effective in maximising the eventual reach of that content. While van der Lans et al [10] developed a model to examine, in part, the effect that different seeding strategies would have on the viral dissemination of content. This focus on campaign seeding is perhaps a reflection of the difficulties associated with developing or managing other elements of viral marketing campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, efforts to effectively measure and model viral marketing processes have been hampered by data availability issues. Thus, to date, analytical approaches for examining viral marketing mechanisms have typically employed pure simulation techniques [42], used simulation techniques when examining actual campaigns to estimate those data points for which no data was available [10,36], conducted self-report studies of intentions [7], or examined contexts that approximate viral marketing [43]. Each of these approaches is characterized by various restrictions that limit the accuracy or generalization of the study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Termin viralni marketing opisuje fenomen kojim potrošači međusobno dele i šire informacije bitne za marketing, koje su prvenstveno poslate namerno od strane marketing menadžera kako bi se stimulisalo prenošenje poruka od osobe do osobe [19]. Viralni marketing je marketinška tehnika koja koristi društvene mreže za proizvodnju povećanja svesti o brendu, kroz samostalno ponavljanje viralne poruke, analogno širenju patoloških i kompjuterskih virusa [13].…”
Section: Marketing Od Osobe Do Osobeunclassified
“…Marketing menadžeri mogu da biraju tri različita načina za započinjanje svoje kampanje viralnog marketinga [19]:  Imejl strategija  Strategija onlajn reklamiranja  Strategija oflajn reklamiranja Da bi se sprovela strategija viralnog marketinga potrebno je adekvatno sprovesti sledeće korake [11]:  Kreiranje strategije i ideje koja će se širiti -potrebno je jasno definisati ideju, cilj i krajnje rezultate kampanje.  Kreiranje prilagođenog sadržaja -odabrati medijum i pripremiti poruku u skladu sa zahtevima tog medijuma.…”
Section: Načini Sprovođenja Strategije Viralnog Marketinga Na Internetuunclassified